DETERMINANTS OF EMPLOYEE RETENTION IN HOSPITALS: THE MEDIATING ROLE OF EMPLOYEE ENGAGEMENT, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, AND WORK-LIFE BALANCE - M. Arwani; Sagita Candra Puspitasari; Mochammad Malik Ibrahim (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Employee retention in healthcare organizations has become an important strategic concern because it is closely related to the continuity of service quality, patient safety, and the overall stability of organizational performance. High levels of turnover among healthcare workers can lead to increased recruitment and training costs, interruptions in service delivery, and a decline in organizational effectiveness. Consequently, identifying the factors that influence employee retention in hospital settings is essential. Objective: This study investigates the influence of transformational leadership on employee retention by incorporating the mediating roles of employee engagement, work-life balance, and organizational citizenship behavior among employees. Method: The research applied a quantitative method with a cross-sectional design. The study population included 621 hospital employees, from which 243 respondents were selected using a purposive sampling technique. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Result; The findings reveal that transformational leadership significantly affects employee engagement and work-life balance, but does not have a direct impact on employee retention. Employee engagement was found to significantly influence both organizational citizenship behavior and employee retention. Moreover, work-life balance and organizational citizenship behavior also demonstrated significant effects on employee retention. These results suggest that employee retention is largely shaped by psychological processes and organizational behaviors that emerge within the workplace environment. Conclusion: Therefore, enhancing leadership practices, strengthening employee engagement, and promoting a supportive work-life balance and positive organizational culture are essential strategies for improving employee retention in hospital organizations.